Decrements in knee extensor and flexor strength are associated with performance fatigue during simulated basketball game-play in adolescent, male players - Scanlan, A. T.; Fox, J. L.; Borges, N. R.; Delextrat, A.; Spiteri, T.; Dalbo, V. J.; Stanton, R.; Kean, C. O. (Journal of Sports Sciences, 2018)
This study quantified lower-limb strength decrements and assessed the relationships between strength decrements and performance fatigue during simulated basketball. Ten adolescent, male basketball players completed a circuit-based, basketball simulation. Sprint and jump performance were assessed during each circuit, with knee flexion and extension peak concentric torques measured at baseline, half-time, and full-time. Decrement scores were calculated for all measures. Mean knee flexor strength decrement was significantly (P < 0.05) related to sprint fatigue in the first half (R = 0.65), with dominant knee flexor strength (R = 0.67) and dominant flexor:extensor strength ratio (R = 0.77) decrement significantly (P < 0.05) associated with sprint decrement across the entire game. Mean knee extensor strength (R = 0.71), dominant knee flexor strength (R = 0.80), non-dominant knee flexor strength (R = 0.75), mean knee flexor strength (R = 0.81), non-dominant flexor:extensor strength ratio (R = 0.71), and mean flexor:extensor strength ratio (R = 0.70) decrement measures significantly (P < 0.05) influenced jump fatigue during the entire game. Lower-limb strength decrements may exert an important influence on performance fatigue during basketball activity in adolescent, male players. Consequently, training plans should aim to mitigate lower-limb fatigue to optimise sprint and jump performance during game-play.